Approach to Refractory Hypoglycaemia in a Patient with Hepatocellular Carcinoma: A Case Study and Literature Review - Audy Meutia Ariana; Ganjar Adityo Permadi; Hermawan Susanto (Faculty of Medicine, Universitas Jember, 2024)
Symptomatic hypoglycaemia in patients without underlying diabetes is uncommon. Etiology of non-diabetic hypoglycaemia varies from hyperinsulinism, hormone deficiencies, malignancies, to critical illness. This case report illustrates the attempt to determine the cause of refractory hypoglycaemia in a 46 years old male patient with underlying hepatocellular carcinoma (HCC). Anamnesis and examinations have narrowed differential diagnosis to concurrent systemic illness (liver failure due to HCC) or paraneoplastic syndrome from non-beta cell tumors, referred as non-islet cell tumor hypoglycaemia (NICTH). It was noted that the absence of chronic liver disease stigmata has put NICTH as the possible main cause. Deciding what diagnostic modalities needed to perform to establish the diagnosis eventually relies on clinical judgement while taking cost-effectiveness and patients’ preference in consideration, particularly in low-resource settings. Nonetheless, the main goal of treating hypoglycaemia is to immediately achieve and sustain euglycemia which can be achieved conservatively or definitively with surgery despite the etiology. Keywords: Hepatocellular carcinoma, Hypoglycaemia, NICTH.